PAKET CEPAT (PACE): INOVASI PELAYANAN PEMDA LAMONGAN - Rozikin, Mochammad (Jurnal Likhitaprajna, 2019)
Competitive value and excellence are always driven to create the best service, quality to all stakeholders by the government, including the Regional Government with the SKPD. Regional autonomy coupled with decentralization is intended to make the government closer to its citizens so that the local government quickly responds to the problems that are developing to find out the solution to the solution. Each Regional Government wants its area to be said to be friendly to investors, because with investors opening its business (production) in the area, several benefits are obtained, such as: opening up employment, developing economic dynamics, living area markets, local revenue (PAD) expected to increase. This paper narrates the results of research in the Lamongan District Government in 2016, the Regional Investment and Licensing Agency, with focus 1) Public service innovation policies by the Regional Government, and 2) Public service innovations conducted by SKPD. Data analysis uses Nine steps from Strauss and Corbin (1990) and Neuman (2000).Â  The results of his research are: 1) Local governments are very responsive to the support of policy innovations, both in the form of product policies (Regent Regulations), funding, institutions and reward rewards for SKPD that innovate after the assessment is conducted. 2) Innovations carried out by the Agency include concepts, mindset, SOP and service promises "PACE" (Quick Package).Keywords: Quick Package, Innovation, Service